Soil amendments and molybdenum on yield and quality of black pepper (Piper nigrum) - Hamza, S; Sadanandan, A K (The Indian Journal of Agricultural Sciences, 2005)
A study was conducted during 1996-99 at Calicut under green house and field in Mo deficient acidic soils to study the effect of soil amendments (lime, farmyard manure) and Mo on soil availability, plant uptake, yield and quality of black pepper (Piper nigrum L.). Under the greenhouse condition, soil application of Mo @ 0.25 mg/kg of soil enhanced the yield and quality of black pepper. Among the amendments farmyard manure @ 100 g/pot enhanced the yield while lime @ 20 g/ pot increased the piperine content by 4.2%. Under field condition, lime application (0.5 tonne/ha) gave significantly highest yield and benefit : cost ratio (4.58). The Mo availability in the soil was highest for soil application of lime (0.5 tonne/ha) followed by Mo @ 0.5 kg/ha.